Травматичний досвід Першої світової війни в щоденнику Володимира Винниченка: катеринославські рефлексії - Нарівська, В.Д. (Слово і Час, 2019)
У статті аналізуються щоденникові записи відомого українського письменника, художника, політичного діяча Володимира Винниченка (1880 – 1951), що висвітлюють початок Першої світової війни. Предмет розгляду – специфіка авторського осмислення масового травматичного досвіду перших днів війни, пережитих письменником у Катеринославі (нині Дніпро). Розкривається вплив травми війни як на масову свідомість, що виявився в радикальній зміні моделі людської поведінки, так і на свідомість творчу, екфрастичну, реалізовану у формуванні основ нового художньо-естетичного і щоденникового мислення. The paper analyzes the diaries by the famous Ukrainian writer, artist and political leader Volodymyr Vynnychenko (1880–1951) that highlight events of the World War I. The idea to start the diary just at that time was interpreted by the author himself as an event of his artistic life, ‘a philosophy of action’. It determined the presence of such notions as ‘attention’, ‘a stop above the life’, ‘moments of life’, ‘a beam of light’ used as philosophic prolegomena in the notes about war and traumatic experience of its first days, which the writer faced in Katerynoslav (now Dnipro). The depth of traumatism is evident against the background of the idyllic records from the Dniper steamship, combined with romantic and patriarchal Gogol-like allusions. The writer noted the transition to the Katerynoslav events carefully and clearly. As a politician he was interested in the conditions of workers, labor unrest, Black-Hundred outrage and the city’s perception of the beginning of the war as a trauma. The author of the diary didn’t separate himself from this tragic fiow of events. He experienced these events directly and deeply, making correspondent records. It was the image of the station full of people leaving for the battlefield that demonstrated the trauma penetrating into the depth of the human consciousness, deforming the general state and behavior. The experience of the diarist led him to conclusion that not only Sarajevo, but also Katerynoslav was the point of the war. The epicenter of the events is in the notes on the station scenes that clearly divided the world into the lost peace and war, causing dramatic changes in human consciousness and behavior. This awareness was facilitated by the successful use of techniques belonging to naturalism, realism, impressionism, and expressionism.